Strategi Peningkatan Sumber Daya Manusia dalam Pencapaian Kinerja Karyawan - Sugiyono Sugiyono (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Human resource management is a process of dealing with various problems within the scope of employees, employees, workers, managers and other workers to be able to support the activities of an organization or company in order to achieve predetermined goals. The aim of the writing is to determine the role of human resource management in organizations by explaining cognitive abilities (X1) on employee work performance (Y1), explaining the influence of emotional abilities (X2) on employee performance abilities (Y1), explaining physical abilities (X3) on employee performance (Y1). The results show that the influence of abilities on employee performance is significantly positive, this means that if the ability variable is increased, employee work performance will also increase.